E-016 A Comparative Review of the Hemodynamics and Pathogenesis of Cerebral and Abdominal Aortic Aneurysms: Lessons to Learn From Each Other. (26th July 2014) - Tanweer, O; Wilson, T; Metaxa, E; Riina, H; Meng, H
Abstract : Introduction/purpose: Cerebral aneurysms (CAs) and abdominal aortic aneurysms (AAAs) are both degenerative vascular pathologies that manifest as an abnormal dilation of the arterial wall. They arise with different morphologies in different types of blood vessels under different haemodynamic conditions. Although these aneurysms are treated as very different and separate pathologies, we sought to examine common pathways in the haemodynamic pathogenesis to further elucidate mechanisms of formation. Materials and methods: A systematic review of the literature was performed. Current concepts on the pathogenesis and hemodynamics of CAs and AAAs were collected and compared. Results: CAs arise as saccular (berry-like) dilation on the cerebral arteries of the circle of Willis under high blood flow, high wall shear stress (WSS), and high wall shear stress gradient (WSSG) conditions. AAAs arise as fusiform (spindle-like) dilations on the infrarenal aorta under low blood flow, low, oscillating WSS, and high WSSG conditions. While the two pathologies exist at likely the opposite ends of the spectrum of WSS, they both share high WSSG. These changes in blood flow have been shown to be a critical factor of introducing arterial remodeling. It is possible that the unique haemodynamic environments in which CAs and AAAs arise cause mechanical damage to the arterial wall. This mechanical damage alone may not be enough to initiate the aneurysm formation, but may ignite a cascade of downstream events that lead to the development of aneurysms. Despite marked differences in their morphology and the structure of the arteries in which they form, CAs and AAAs share many histopathological and biomechanical characteristics. Endothelial cell damage, loss of elastin, and smooth muscle cell loss are universal findings in CAs and AAAs. Increased matrix metalloproteinases and other proteinases as well as reactive oxygen species likely play an important role in the pathogenesis of both CAs and AAAs. Inflammation, which plays an integral role in the initiation of AAAs, seems to play a stronger role in CAs downstream from initiation events. Conclusion: A critical review of the literature revealed similar pathways in two seemingly different pathologies. Specifically, the roles of WSSG, inflammation and sequences of endothelial dysfunction play an important role in both AAA and CA formation. We also highlight the need for cross-disciplinary reviews that help aid in finding similar threads between pathologies. Disclosures: O. Tanweer: None. T. Wilson: None. E. Metaxa: None. H. Riina: None. H. Meng: None.